Existence Results for Nonoscillatory Solutions of Third Order Nonlinear Neutral Difference Equations - Thandapani, E.; Karunakaran, R.; Arockiasamy, I. M. (Sarajevo Journal of Mathematics, 2024)
In this paper the authors consider the third order neutral difference equation equation* Δ ^3( x_n+p_nx_n-k) +q_nf( x_n-) =h_n equation* where { p_n} ,{ q_n} ,{ h_n} are real sequences. They use Krasnoselskii's fixed point theorem to establish the existence of nonoscillatory solutions. The results are illustrated with examples. 2000 Mathematics Subject Classification. 39A10